A very rare case of possible actinomycosis of the mandible from the Middle Ages - Vargová, Lenka; Horáčková, Ladislava; Vymazalová, Kateřina; Němečková, Alena; Tvrdý, Zdeněk; Galuška, Luděk; Mitáček, Jiří; Fialová, Dana (International journal of paleopathology, 2020)
OBJECTIVE: Documented cases of actinomycosis in archaeological skeletons are very rare, especially from Central Europe. Our contribution will help facilitate the differential diagnosis of this disease for other paleopathologists. MATERIAL: This paper describes a pathological finding of the skeleton of a 40-year-old male from a burial ground in Sady-Špitálky (Czech Republic) dated to the 10th-12th century. METHODS: The affected skeleton was evaluated as a probable case of actinomycosis on the basis of a detailed macroscopic, X-ray and histological examination. The osteolytic foci examined were compared with similar changes caused by tuberculosis, syphilis and mycoses. RESULTS: The character and location of the defect on the mandible is indicative of organ actinomycosis and is also reflected by the lytic lesion observed on a lumbar vertebra. CONCLUSIONS: The described case can be considered one of the very rare paleopathological findings of possible actinomycosis in humans in Central Europe. SIGNIFICANCE: Good evidence of bone actinomycosis findings may be beneficial for further paleopathological and epidemiological studies, especially for research focused on the diachronic development of actinomycosis in Europe. In doing so, all available factors, such as hygiene habits, nutrition, social structure and overall health of the population that could be causally related to its origin, course and treatment, can be taken into account. LIMITATIONS: The mandible of the studied individual was damaged, especially in the area affected by the lesion, so the paleopathological analysis was difficult to perform. SUGGESTION FOR THE FUTURE RESEARCH: In future, actinomycosis in this skeleton may be confirmed by bio-molecular analysis.
Keywords: paleopatologie; aktinomykóza; dospělí; History, Medieval; Česká republika; Paleopathology; lidé; mandibula; mužské pohlaví; Actinomycosis; Male; Mandible; Czech Republic; Adult; dějiny středověku; Humans